The Art of Diagnosis from Breath Sound: A Literature Review - Ambun Suri Afdi, Tania Libristina; Sri Indah Indriani (HM Publisher, 2024)
Breath sounds provide relevant information related to lung abnormalities. It is often difficult to differentiate between breath sounds, this is due to the different characteristics of each breath sound. Differentiating the types of breath sounds is crucial in making an accurate diagnosis. Breath sounds are divided into normal breath sounds and abnormal (additional) breath sounds. Normal breath sounds are sounds that originate from the chest wall, such as tracheal, bronchial, bronchovesicular and vesicular breath sounds. Meanwhile, abnormal (additional) breath sounds are breath sounds that indicate an abnormal condition in the respiratory system. Normal and abnormal breath sounds have different characteristics such as intensity, duration, frequency, quality of air flow, air flow pattern, air distribution, body position, location of sound production, changes in pressure and vibration of dense tissue in the lungs.